Respuesta :
this is actually pretty easy.
Simplifying 4n + -9 = -9 Reorder the terms: -9 + 4n = -9 Add '9' to each side of the equation. -9 + 9 + 4n = -9 + 9 Combine like terms: -9 + 9 = 0 0 + 4n = -9 + 9 4n = -9 + 9 Combine like terms: -9 + 9 = 0 4n = 0 Solving 4n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '4'. n = 0 Simplifying n = 0
****hope this helps!!!! please put as brainliest if possible!!!! really appreciated!!
Simplifying 4n + -9 = -9 Reorder the terms: -9 + 4n = -9 Add '9' to each side of the equation. -9 + 9 + 4n = -9 + 9 Combine like terms: -9 + 9 = 0 0 + 4n = -9 + 9 4n = -9 + 9 Combine like terms: -9 + 9 = 0 4n = 0 Solving 4n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '4'. n = 0 Simplifying n = 0
****hope this helps!!!! please put as brainliest if possible!!!! really appreciated!!